Improving the Quality of Freedia Herbal Products SME Hippocrates Medika Palembang with the Application of Capsulation Technology - Hidayat, Rachmat; Hayati, Lusia; Parisa, Nita; Purnamasari, Septi; Inggarsih, Rara (Indonesian Community Empowerment Journal, 2022)
Spices have been widely developed for herbal products because people believe that the product is safe without any side effects that are harmful to the health of the body. Herbal products are made from natural ingredients of plants or plants without a mixture of chemicals. One of the herbal product businesses in Palembang is SME Hippocrates Medika. SME Hippocrates Medika was established in 2019 as a communal partnership. Freedia is the mainstay product of this SME, which is downstream from the innovative products of Rachmat Hidayat and the team. Freedia is an herb that is processed as a brewed drink to overcome diabetes mellitus disorder. In an effort to improve the quality of Freedia products, efforts are made to carry out a capsulation process for the extract so that the discomfort of freedia extract can be minimized to the maximum. The application of capsulation technology greatly helps improve the quality of freedia herbal products. Where consumers feel very comfortable in the consumption of freedia herbs because there is no need to bother boiling herbs, and do not need to feel bitter when consuming herbs.